2019
DOI: 10.26508/lsa.201800278
|View full text |Cite
|
Sign up to set email alerts
|

A network of human functional gene interactions from knockout fitness screens in cancer cells

Abstract: Genetic interactions mediate the emergence of phenotype from genotype. The systematic survey of genetic interactions in yeast showed that genes operating in the same biological process have highly correlated genetic interaction profiles, and this observation has been exploited to infer gene function in model organisms. Such assays of digenic perturbations in human cells are also highly informative, but are not scalable, even with CRISPR-mediated methods. As an alternative, we developed an indirect method of de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 86 publications
3
125
0
Order By: Relevance
“…Previous reports have demonstrated that genes with shared functions, particularly those which encode components of obligate protein complexes, have convergent effects on fitness when deleted in cancer cell lines (Kim et al, 2019;Pan et al, 2018). Consistent with prior analyses performed in few cell lines, network analysis of the strongest coessential relationships in the genome (r>0.6; 1532 pairings) successfully identifies modules of biological relevance with highly correlated fitness profiles ( Figure S1B).…”
Section: Assembling a Coessentiality Network Around The Master Regulasupporting
confidence: 80%
See 2 more Smart Citations
“…Previous reports have demonstrated that genes with shared functions, particularly those which encode components of obligate protein complexes, have convergent effects on fitness when deleted in cancer cell lines (Kim et al, 2019;Pan et al, 2018). Consistent with prior analyses performed in few cell lines, network analysis of the strongest coessential relationships in the genome (r>0.6; 1532 pairings) successfully identifies modules of biological relevance with highly correlated fitness profiles ( Figure S1B).…”
Section: Assembling a Coessentiality Network Around The Master Regulasupporting
confidence: 80%
“…Great insights have been gained from pairwise genetic screens in model organisms, most prominently budding yeast (Costanzo et al, 2016), but the larger human genome has proved challenging for genome-wide combinatorial study of genetic perturbations. With the advent of high quality CRISPR-Cas9 screening libraries in recent years, the coessentiality approach has emerged as an alternative to pairwise genetic perturbations for the discovery of novel genes and genetic interactions (Boyle et al, 2018;Kim et al, 2019;Pan et al, 2018). These first coessentiality studies detail a top-down approach which effectively resolves major protein complexes and identifies functional clusters in the genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue that originated a tumor is well known to be a major determinant of drug responses -- including drugs targeted to certain genetic mutations -- both in vitro (11,12) and also in vivo (15,16). Tissue of origin is an important factor in shaping the networks of genetic interactions in cancer (17) and also determines the phenotypes resulting from genetic perturbation (18). Therefore ascertaining the tissue/cell type identity of cell lines is relevant for interpreting results of various experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted small molecules often don't discriminate, or discriminate poorly, between closely related paralogs, and it may be their promiscuity rather than their specificity that renders them effective. For example, MEK inhibitor trametinib effectively targets the protein products of both MAP2K1 and MAP2K2, redundant kinases downstream of RAS/RAF oncogenes, but the functional redundancy of these genes renders them both invisible to monogenic CRISPR screens, even in RAS/RAF backgrounds (Kim et al, 2019). A systematic survey of paralogs families, in particular those with only two family 460 members that are constitutively expressed, for synthetic lethality could unmask this genetic buffering and yield greater insight into the constellation of targetable genes in a tumor.…”
mentioning
confidence: 99%